Orthodontic management of a case with skeletal Class III malocclusion (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
Class III malocclusions are considered one of the most complex and difficult orthodontic problems to diagnose and treat. Skeletal and/or dental asymmetries in patients presenting with Class III malocclusions can worsen the prognosis. Recognizing the dentoalveolar and skeletal characteristics of Class III malocclusions and their treatment possibilities is essential for a favorable nonsurgical correction. Therefore, this article presents a nonsurgical extraction approach to Class III malocclusion treatment which can significantly improve the occlusal and facial discrepancies. DOI: http://dx.doi.org/10.3329/bjodfo.v2i1.15999 Ban J Orthod & Dentofac Orthop, October 2011; Vol-2, No.1, 20-25